HEALTH AND SAFETY ON COMPANY PERFORMANCE AT PT LEIGHTON CONTRACTOR INDONESIA (LCI) IN LIKUPANG - Montolalu, Chirsthen; Lapian, S. L.H.V (FEB Universitas Sam Ratulangi Manado, 2014)
Organizations and companies that smart enough to realize about the importance of health and safety started to give more attention to their organizational and management impact on safety performance particularly the function of health and safety. Health and safety have an important role in organizations profit. Profit margins are higher among the organizations with better on their health and safety management. This study aimed to find out does health and safety have an influence on company performance at PT. Leighton Contractors Indonesia. The type of this research is associative research and uses causal type of research where it is designed to determine whether health and safety have an influence or affects the company performance.The result shows that health and safety have an influence on company performance based on the influence analysis also health and safety and company performance have a strong relationship as shown in coefficient correlation. The result shows that health and safety influence the company performance simultaneously and partially. It is better for the management of the company to maintain the employees to keep following the rules of health and safety and if it is able, the company can improve the policy of health and safety. Keywords: health, safety, company performance